2022
DOI: 10.3389/fmed.2022.971481
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dementia literacy and caregiving appraisal on the psychological wellbeing of informal caregivers of people with dementia: A cross-sectional study

Abstract: BackgroundDementia informal caregiving is a global phenomenon. It is well documented that caregivers' psychological health is often affected by busy caregiving schedules. Lawton's two-factor model indicates that caregivers' psychological wellbeing is influenced by caregiving appraisal and other caregiver factors. Our review also identified the significance of dementia literacy, which was an essential caregiver factor. However, it is imperative for a clear understanding of the mechanism of how psychological wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This study aims to enhance the psychological well-being of informal caregivers of people with dementia through an accessible, easy-to-use, and sustainable intervention that overcomes caregivers’ barriers to participating in psychosocial interventions. The e-bibliotherapy protocol is developed based on solid evidence, including a series of systematic reviews, surveys among informal caregivers of people with dementia, and a pilot study [ 6 , 12 , 17 , 19 , 35 ]. Our program aligns with the imperative of implementing interventions that address the critical problems among dementia caregivers identified by other publications, and the intervention components cover different emergent needs of caregivers [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study aims to enhance the psychological well-being of informal caregivers of people with dementia through an accessible, easy-to-use, and sustainable intervention that overcomes caregivers’ barriers to participating in psychosocial interventions. The e-bibliotherapy protocol is developed based on solid evidence, including a series of systematic reviews, surveys among informal caregivers of people with dementia, and a pilot study [ 6 , 12 , 17 , 19 , 35 ]. Our program aligns with the imperative of implementing interventions that address the critical problems among dementia caregivers identified by other publications, and the intervention components cover different emergent needs of caregivers [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our survey of Chinese dementia caregivers revealed that their psychological well-being was unsatisfactory, characterized by low autonomy and low environmental mastery. This was particularly evident during the COVID-19 pandemic, with 72.1% of caregivers experiencing clinical or major depression, in addition to high levels of stress [ 12 ]. Another study found that approximately 80% of working dementia caregivers felt depressed or hopeless, and 60.8% reported poor or fair health status [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight negatively stated items were rated inversely. Total scores ranged from 18 to 108, with a predefined cut-off of low (18 to 53), moderate (54 to 89), and high (90 to 108) (Wang et al, 2022).…”
Section: Scale Of Psychological Well-beingmentioning
confidence: 99%
“…Over 80% of caregivers experience stress, anxiety, and depression [13], with studies in Hong Kong indicating a burnout rate of 15.5% among them [14]. The continuous demands of caregiving, along with personal career and social sacri ces, severely impact caregivers' mental health and QoL [15]. China's cultural and societal factors intensify the challenges faced by home caregivers, leading to signi cant knowledge and support gaps compared to institutional care [10].…”
Section: Introductionmentioning
confidence: 99%